2018
DOI: 10.1002/ijc.31323
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the urinary metabolic variations and the application in bladder cancer biomarker discovery

Abstract: Urine metabolomics have been used to identify biomarkers for clinical diseases. However, inter-individual variations and effect factors need to be further evaluated. In our study, we explored the urine metabolome in a cohort of 203 health adults, 6 patients with benign bladder lesions, and 53 patients with bladder cancer (BCa) using liquid chromatography coupled with high resolution mass spectrometry. Inter-individual analysis of both healthy controls and BCa patients showed that the urine metabolome was relat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
41
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 57 publications
(50 citation statements)
references
References 50 publications
9
41
0
Order By: Relevance
“…In the present study, we characterized the urine metabolomes of males and females in children and adults. Consistent with previous studies [4,6,7], amino acid metabolism, including tryptophan metabolism and arginine and proline metabolism, showed gender differences in both children and adults.…”
Section: Gender-dependent Metabolism Status In Children and Adultssupporting
confidence: 92%
See 2 more Smart Citations
“…In the present study, we characterized the urine metabolomes of males and females in children and adults. Consistent with previous studies [4,6,7], amino acid metabolism, including tryptophan metabolism and arginine and proline metabolism, showed gender differences in both children and adults.…”
Section: Gender-dependent Metabolism Status In Children and Adultssupporting
confidence: 92%
“…Most of the speci c gender-dependent metabolites in adults showed higher levels in males, including fatty acids, acylcarnitines, steroid hormones and dipeptides. Higher levels of acylcarnitines in males were found in our previous study, indicating a higher activity of fatty acid oxidation and energy production in males compared to females [7]. In addition, a higher level of steroid hormone biosynthesis was found in males, consistent with previous studies [17].…”
Section: Gender-dependent Metabolism Status In Children and Adultssupporting
confidence: 91%
See 1 more Smart Citation
“…It has been qualified as a part of model of bladder cancer grading distinction. As the increase of pathologic stage malignant degree of gallbladder, the concentration of IAcrGly decreased in high-grade bladder cancer compared with low-grade bladder cancer 60 . Herein, a significant decrease of urinary concentration of IAcrGly in CRC patients was also found.…”
Section: Discussionmentioning
confidence: 90%
“…Females are diagnosed more frequently with a more progressive stage of the disease and display poorer treatment results after cystectomy and a higher risk of disease reoccurrence in comparison to males, a fact that may be explained by earlier invasion and progression. Moreover, it has been proven that estrogen, estrogen receptor, testosterone and dihydrotestosteron (34)(35)(36) as well as androgen receptor (37) are involved in BCa development. It has been reported that loss of androgen receptor expression was correlated with the progression of BCa stage (5).…”
Section: Concentration Of Aromatase [Ng/ml] -------------------------mentioning
confidence: 99%